A efetividade dos mecanismos de prevenção e punição de execuções sumárias: vivências do CDHS de Sapopemba - Silva, Damazio Gomes da (2022)
This work aims to promote reflection on the role of the Brazilian Rule of Law in the protection of life and human freedom. Since ancient times, the right to life has always been subject to laws and religious principles, later becoming a right protected by the modern State. However, although there is a weakness in the protection of rights by certain States with regard to the right to life and human freedom, the fact is that, in the 21st century, the struggle for rights becomes necessary, so that the right to life be the basic principle of all other rights that may arise from it, with the observance and respect of the entire international community